Persepsi Masyarakat Perkotaan dan Pedesaan Terhadap Perbankan Syariah. - Kasmiah Mia; St Fitri; Fitri Kumalasari; Andi Muttaqin Mufti (IAI Al-Mawaddah Warrahmah Kolaka, 2019)
Islamic banks still lack encouraging growth, both network and business volume, compared to the growth of conventional banks. This is indicated by the small number of Islamic banks, especially in Kolaka Regency. Islamic banks in Kolaka Regency are only 2 (two) Islamic banks, namely Bank Muamalat Tbk Kolaka and Bank BNI Syariah Kolaka. The majority of the Kolaka Regency community is Muslim. But the public's knowledge about Islamic banks in Kolaka Regency, especially in rural areas, it is still very limited. Urban communities regarding their knowledge about Islamic banks are well known. Because, there are already urban people who make every transaction in Islamic banks and urban communities feel that Islamic banks do indeed have to be further enhanced according to the teachings given by Allah SWT the perception of urban and rural communities there is no significant difference. Because, the urban community's knowledge of Islamic banks is only limited to savings products that are superior in society while other products are still lacking in knowledge as well as rural